2019
DOI: 10.1039/c8dt04351e
|View full text |Cite|
|
Sign up to set email alerts
|

Investigation on the structure and thermoelectric properties of CuxTe binary compounds

Abstract: The thermal conductivity of Cu2Te is around 4 W m−1 K−1 at 300 K with low Cp values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 31 publications
4
46
2
Order By: Relevance
“…[1,4,42,43] This chemical flexibility yields a complex copper telluride system (similar to those of Cu 2−x S and Cu 2−x Se) with different compositions and crystal structures possible, including stoichiometric extremes orthorhombic CuTe and hexagonal Cu 2 Te, as well as nonstoichiometric Cu 2−x Te. [13,44] Here, we assign the crystal phase of Cu 2−x Te NCs synthesized at lower temperatures to the recently reported Cu 31 Te 24 (Cu 1.29 Te) structure. [45] A structural model is provided in Figure S6b, Supporting Information.…”
Section: Phase Transition and Morphology Control Of Cu 2−x Te Nanocrysupporting
confidence: 58%
“…[1,4,42,43] This chemical flexibility yields a complex copper telluride system (similar to those of Cu 2−x S and Cu 2−x Se) with different compositions and crystal structures possible, including stoichiometric extremes orthorhombic CuTe and hexagonal Cu 2 Te, as well as nonstoichiometric Cu 2−x Te. [13,44] Here, we assign the crystal phase of Cu 2−x Te NCs synthesized at lower temperatures to the recently reported Cu 31 Te 24 (Cu 1.29 Te) structure. [45] A structural model is provided in Figure S6b, Supporting Information.…”
Section: Phase Transition and Morphology Control Of Cu 2−x Te Nanocrysupporting
confidence: 58%
“…62 Raman spectra collected from our platelets heated ex situ (Figure S4C) also indicate that the final material is Cu 2Àx Te (with x between 0 and 0.4). 61 Finally, the XPS spectra for the platelets heated ex situ show signatures of Cu 0 and Cu 1+ (Figures S4D-S4F), which further suggests the transformation to Cu 2Àx Te. Despite the uncertainty of the crystal structure, our data imply that the general transformation of Cu-intercalated Bi 2 Te 3 to Cu 2Àx Te is applicable to other conditions beyond high vacuum.…”
Section: Resultsmentioning
confidence: 85%
“…The Cu 2 Te crystals have a layered hexagonal crystal structure with a P3m1 space group. 60,61 We note that Cu 2Àx Te compounds are known to exhibit slightly substoichiometric compositions (Cu deficiency), which allows for a variety of closely related but distinct crystal structures, and recent DFT calculations have shown that Cu 2Àx Te can exhibit low-energy monoclinic and trigonal structures. 62 We index the observed material in Figure 3 to the P3m1 structure due to the close match to the expected SAED peaks, as well as the Cu/Te ratio that is close to 2.0 (1.9:1), as detailed subsequently in Figure 6.…”
Section: Resultsmentioning
confidence: 99%
“…Previously reported copper telluride bulk and thin film samples (Mansour et al, 1986;Nethravathi et al, 2014;Ghosh et al, 2016;Mukherjee et al, 2019;Mukherjee et al, 2020) exhibited relatively low Seebeck coefficients of between 4 and 40 μV K −1 . While electrodeposited Cu 0.5 Te showed a particularly high Seebeck coefficient (346 μV K −1 ), the Cu 0.5 Te thin film is extremely poorly electrically conductive, which results in a low power factor (2.48 μW cm −1 K −1 ).…”
Section: Electrical and Thermoelectrical Properties Of Electrodeposited Copper Telluride Thin Filmsmentioning
confidence: 96%
“…Table 1 lists the thermoelectric properties of the electrodeposited thin films and others reported in the literature (Mansour et al, 1986;Nethravathi et al, 2014;Ghosh et al, 2016;Mukherjee et al, 2019;Mukherjee et al, 2020), including Seebeck coefficients, conductivities, and calculated power factors. The electrodeposited thin films have somewhat larger Seebeck coefficient than their bulk counterparts.…”
Section: Electrical and Thermoelectrical Properties Of Electrodeposited Copper Telluride Thin Filmsmentioning
confidence: 99%